Need for Distinctiveness Leads to Pathological Internet Use? The Perspective of Cognitive Behavioral Model - Zeng Wei; Wei Hua; Liu Meiting (MDPI, 2025)
Based on the cognitive behavioral model of pathological Internet use and the gender role theory, this present study investigated the association between the need for distinctiveness and pathological Internet use. Additionally, we explored a mediating role of maladaptive cognition in the association between the need for distinctiveness and pathological Internet use and tested whether the mediation model was moderated by gender. A sample of 745 Chinese university students (Mage = 19.92, SDage = 1.42) was studied and participants completed anonymous questionnaires regarding the need for distinctiveness, maladaptive cognition, and pathological Internet use. Results revealed that the need for distinctiveness was positively associated with pathological Internet use, and the association between the need for distinctiveness and pathological Internet use was mediated by maladaptive cognition. In addition, gender moderated the association between maladaptive cognition and pathological Internet use; the effect was stronger for female participants than male participants. The findings expanded our understanding of the dark side of seeking distinctiveness. Practically, the results suggest that policymakers and psychological practitioners consider gender in preventing and intervening in pathological Internet use.